2017
DOI: 10.1080/0167482x.2017.1296428
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ beliefs about the causes of myomas: a pilot study from a large European city

Abstract: It is curious that two of the four most common explanations for myomas were stress and somatization, and were endorsed by nearly half of all patients. Physicians seeing women for myomas should consider that many such patients may have further hidden reasons for seeking medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…As in other studies concerning patients with tumors, irritable bowel syndrome or fibroids, the proportion of patients who agreed to at least one possible subjective theory of illness when completing a standardized questionnaire such as the IPQ-R was very high (over 90%). 14,31,32…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As in other studies concerning patients with tumors, irritable bowel syndrome or fibroids, the proportion of patients who agreed to at least one possible subjective theory of illness when completing a standardized questionnaire such as the IPQ-R was very high (over 90%). 14,31,32…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on subjective theories of illness in fibroid patients also confirmed stress as a frequently mentioned factor. 14 According to the only published study on subjective theories of illness in endometriosis patients to date, one in eight women assumed that the cause of their illness was prioritizing their career. 16 Stress as a cause of illness is receiving more and more attention, and the notion of stress is now thought to be dominant in our culture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations